THE EFFECT OF LPG USING RATIO ON PERFORMANCE AND EMISSION CHARACTERISTICS IN A SPARK IGNITION ENGINE WITH DUAL FUEL INJECTION - (:unkn) unknown (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2009)
In this study, the effect of LPG using ratio on engine performance, emissions and fuel economy in a spark ignition engine with gasoline and LPG injection systems was investigated. For this purpose, a vehicle has four cylinder spark ignition engine was modified to able to operate with duel fuel. Amount of injection fuels were calculated to obtain same heat value in the duel fuels operation. Experiments were applied in the vehicle dynamometer at different LPG using ratios (as heat value 0%, 25%, 50%, 75%, 100%), constant revolution (3800 d/d) and different load ratios (5%, 30%, 60%, 90%). Experiments gave affirmative results with regard to exhaust emissions and fuel economy at all LPG using ratios. However, positive results were only obtained at 25% LPG using ratio with respect to engine performance.
Keywords: Alternative fuels; dual fuel; LPG; gasoline; engine performance; emissions; GAS